Structural arrangement of beginnings and endings in later novels by Graham Greene with first person narration - Кальницкая, Виолетта Борисовна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The study deals with the assessment of a semantic relationship between the beginnings and finals in later novels by Graham Greene with first person narration, which in their interrelation are one of the most important sense-bearing aesthetically significant elements. This is primarily demonstrated by the author’s intent to give the details regarding the characters, scene and time of the events from the very beginning of the novel. Finals of the later novels are related to the beginnings thematically and substantively and include philosophical and ethical reflections, which, in turn, echoing the epigraphs, clarify, deepen and broaden aesthetic and semantic content of the novels.